KEBIJAKAN PENINGKATKAN DISPLIN APARATUR SIPIL NEGARA DI KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Alexsander Alexsander; Yuniarti Yuniarti; Adi Sutojo (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2026)
This study aims to analyze the work discipline of Civil Servants (ASN) and to identify its relationship with public service performance at the Pondok Kelapa Subdistrict Office. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Informants included the Subdistrict Head, Subdistrict Secretary, Section Heads, ASN staff, and community members who served as service users. The results indicate that work discipline indicators such as attendance, compliance with regulations, adherence to work standards, level of vigilance, and ethical behavior have generally been implemented fairly well; however, several challenges remain in ensuring consistent application. The implementation of a mobile application-based attendance system has supported attendance monitoring, although it has not fully guaranteed optimal discipline. The identified challenges include the limited comprehensive documentation of Standard Operating Procedures (SOPs), the absence of clearly measurable service time standards, and an informal complaint management system. In terms of public service performance, the aspects of productivity, service quality, responsiveness, and accountability are categorized as fairly good, although further strengthening in standardization, transparency, and performance evaluation based on measurable indicators is still required. The study concludes that systematic and sustainable improvement of ASN work discipline is a crucial factor in supporting more effective, consistent, and accountable public service delivery.